Village Baseline Study: Site Analysis Report for Khulna - Morrelganj, Bangladesh - Shrestha, K.; Rahman, A; Khadka, L; Acharya, Ganesh; Rayamajhi, Arati; Belayat, A; Reza, O (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The Gabgachhia village is located in the coastal region of Bangladesh’s Khulna district. The population is rising and living with high levels of poverty and food insecurity. Local resources that are not critically strained from climate change and poor resource management are few, beyond mosques, roads and schools. The community has seen dramatic changes in resources, as early as 1990, which they attribute to increased population pressures and climate change impacts. Forests have been depleted, rivers are full of silt and lacking life, farmlands have low productivity due to rising salinity, flooding and inappropriate varieties, drinking water is insufficient to meet human, crop and animal needs, and infrastructure is weak and unable to withstand the environment